Concerted loop motion triggers induced fit of FepA to ferric enterobactin - Smallwood, Chuck R.; Jordan, Lorne; Trinh, Vy; Schuerch, Daniel W.; Gala, Amparo; Hanson, Mathew; Shipelskiy, Yan; Majumdar, Aritri; Newton, Salete M.; Klebba, Phillip E. (My University, 2014)
Spectroscopic analyses of fluorophore-labeled Escherichia coli FepA described dynamic actions of its surface loops during binding and transport of ferric enterobactin (FeEnt). When FeEnt bound to fluoresceinated FepA, in living cells or outer membrane fragments, quenching of fluorophore emissions reflected conformational motion of the external vestibular loops. We reacted Cys sulfhydryls in seven surface loops (L2, L3, L4, L5, L7 L8, and L11) with fluorophore maleimides. The target residues had different accessibilities, and the labeled loops themselves showed variable extents of quenching and rates of motion during ligand binding. The vestibular loops closed around FeEnt in about a second, in the order L3 > L11 > L7 > L2 > L5 > L8 > L4. This sequence suggested that the loops bind the metal complex like the fingers of two hands closing on an object, by individually adsorbing to the iron chelate. Fluorescence from L3 followed a biphasic exponential decay as FeEnt bound, but fluorescence from all the other loops followed single exponential decay processes. After binding, the restoration of fluorescence intensity (from any of the labeled loops) mirrored cellular uptake that depleted FeEnt from solution. Fluorescence microscopic images also showed FeEnt transport, and demonstrated that ferric siderophore uptake uniformly occurs throughout outer membrane, including at the poles of the cells, despite the fact that TonB, its inner membrane transport partner, was not detectable at the poles.
Keywords: Ferric enterobactin; FepA; Fluorophore-labeled Escherichia coli; Escherichia coli; Loops